1987
DOI: 10.1093/bja/59.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Catecholamine Responses to Laryngoscopy With and Without Tracheal Intubation

Abstract: The catecholamine and cardiovascular responses to laryngoscopy alone have been compared with those following laryngoscopy and intubation in 24 patients allocated randomly to each group. Following induction with fentanyl and thiopentone, atracurium was administered and artificial ventilation undertaken via a face mask for 2 min with 67% nitrous oxide in oxygen. Following laryngoscopy, the vocal cords were visualized for 10 s. In one group of patients, ventilation was then re-instituted via a face mask, while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
340
1
20

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(410 citation statements)
references
References 9 publications
25
340
1
20
Order By: Relevance
“…The study by Shribman 6 was very similar to our study. However, they found a significant but similar increase in arterial pressure and circulating catecholamine concentrations following laryngoscopy with or without intubation.…”
Section: Discussionsupporting
confidence: 91%
“…The study by Shribman 6 was very similar to our study. However, they found a significant but similar increase in arterial pressure and circulating catecholamine concentrations following laryngoscopy with or without intubation.…”
Section: Discussionsupporting
confidence: 91%
“…Changes in arterial blood pressure and plasma noradrenaline and adrenaline have been shown to be similar, whether or not laryngoscopy is followed by tracheal intubation [7]. These changes may be associated with detrimental physiological effects particularly in those with cardiovascular or cerebrovascular disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…These include a pressor response and tachycardia along with an increase in catecholamine concentrations [I, 4-61. Shribman and colleagues have shown that laryngoscopy alone generates the same pressor and sympathoadrenal responses as larnygoscopy followed by intubation [7]. The major cause of the sympathoadrenal response is believed to arise from stimulation of the supraglottic region by the laryngoscope blade with tracheal tube placement and cuff inflation contributing little additional stimulation [7].…”
mentioning
confidence: 99%
“…has been shown to provide sedation resulting in or from inhibition of CA release in conscious adults, 2~ it is unlikely that oral diazepam (10 mg) premedication attenuates CA changes following intubation in adults. [3][4][5] Thiamylal is a thiobarbiturate which is very similar to thiopentone in chemical structures and 1.1 times as potent as thiopentone. 2] Since two large-scale blinded studies found no difference between these drugs, ~ the difference in potency seems to be too small to achieve no clinical importance.…”
Section: Discussionmentioning
confidence: 99%